PEMBELAJARAN PKN PROJECT CITIZEN DALAM MENINGKATKAN KETERAMPILAN ABAD KE-21 DI SD MUHAMMADIYAH TEMINABUAN KABUPATEN SORONG SELATAN - shela, Didit; Iswatiningsih, Daroe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Civic Education learning through the Project Citizen approach has significant potential in enhancing 21st-century skills among students, such as critical thinking, creativity, communication, collaboration, character, and citizenship. This research was conducted at SD Muhammadiyah Teminabuan, South Sorong Regency, with the aim of exploring the effectiveness of this approach in elementary education. The research methods included direct observation, interviews, and document analysis. The results show that the Project Citizen approach not only enhances active student engagement in learning but also deepens their understanding of citizenship issues, teamwork skills, and the ability to solve social problems with creative solutions. These findings provide valuable insights for curriculum development and learning strategies in elementary schools to prepare students for the challenges of the modern world.